Noise levels at traffic intersections and awareness of noise pollution among traffic policemen and automobile drivers (International Journal of Occupational Safety and Health, 2023)
Introduction: Noise pollution is an important health hazard in modern times and traffic policemen and automobile drivers are exposed to unregulated vehicular noise. This study aims to estimate the exposure levels from traffic noise for traffic policemen and automobile drivers and assess their awareness regarding noise pollution and the use of noise prevention measures.Methods: An analytical cross-sectional study was carried out comprising the exposed and the control group with 121 people in each group. Sound level estimation was carried out across 20 traffic intersections in the city at various times to assess the noise levels. All the participants were administered a pretested questionnaire to assess their awareness regarding noise pollution and as well as the use of noise prevention strategies.  The chi-square test was used to estimate the difference between the two groups. P